Specific drugs for rare diseases in a province of eastern China under catalog management: from 2021 to 2023 - Nie, Ruifang; Zhao, Zhen; Zhang, Yahui; Xu, Bo; Zhang, Wen (Frontiers in Pharmacology, 2025)
BackgroundChina attaches great importance to the prevention and treatment of rare diseases. The government has successively formulated two rare disease catalogs, and approved a variety of rare diseases treatment drugs. However, the actual supply and utilization of these drugs post-marketing remains unclear.MethodsBased on the first and second list of national rare disease catalog in China, this study sort out the specific therapeutic drugs and extract procurement data from the provincial platform over the past 3 years. Subsequently, the drug allocation, shortages, delivery rate, temporal changes, and spatial distribution were analyzed to gain a comprehensive understanding of the local drug supply situation.Results and DiscussionIn the first catalog of 121 rare diseases, China has listed 54 specific drugs; in the second catalog of 86 rare diseases, 35 specific therapeutic drugs have been identified. Among these drugs, Shandong Province has access to 42 and 28, respectively. Spesolimab, Sodium Phenylbutyrate, Nitisinone and Emapalumab are currently in short supply, and the delivery rate of 16 drugs such as Selumetinib, Sirolimus (tablet), Octreotide, Dimethyl Fumarate and Lanreotide is below 80%. The number of available drugs increased year by year. The allocation of 19 drugs increased significantly, and 19 drugs were newly developed. The overall procurement cost of drugs increased and then decreased, which may be related to national policies. Additionally, there are significant regional disparities in drug cost, with Jinan, the provincial capital, leading at 770 million RMB.ConclusionThe number of specific drugs for rare diseases has steadily increased, with the drug availability rate in Shandong Province reaching 80%. This indicates a generally high level of accessibility to drugs for rare diseases in China. However, attention should be given to improving the supply capacity for drugs that are in short supply and have a low delivery rate.